Rock porosity determination in the historical monuments preservation - Labus, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Since ancient times people have used natural stone materials for building purposes. The need of safeguarding historical sites and cultural heritage provoke considering the precise technical characterization of building stones and their changes in weathering processes. In the paper there were listed detailed petrographical analysis used for assessing the quality and durability of the stone material. The porosity properties are detected by means of a range of methods, divided into two groups: direct (including thin section microscopy and scanning electron microscopy), which allow direct documentation and measuring of pore space; and indirect (including mercury porosimetry or nitrogen sorption method), which enable calculating the porosity data from the measuring results.
Keywords: porowatość skał; oznaczanie porowatości skał; zabezpieczanie pomników; rock porosity; determination of rock porosity